Forested wetlands in a protected area and the adjacent working landscape provide complementary biodiversity value based on breeding birds: A case study from Nova Scotia, Canada - John Brazner; Jake Walker; Frances Mackinnon; Rob Cameron (Canadian Science Publishing, 2023)
Protected areas (PAs) are a key component of most conservation strategies because they are thought to enhance biodiversity value relative to similar habitats in working landscapes. To examine whether PAs in Nova Scotia are functioning to enhance the biodiversity value of the landscapes in which they are embedded, we surveyed breeding bird communities in forested wetlands inside and outside of a large PA during 2018 and 2019. We found significantly higher species richness and diversity at sites in the working landscape relative to those inside the PA. Bird communities from different wetland types inside the PA were distinct from each other and those outside the PA, whereas bird communities at outside sites were homogenized and comprised of more early-successional species. There were numerous species of conservation concern at both inside and outside sites, indicating that both types of sites are playing important conservation roles. Abundances of these key species were driven by a combination of local (e.g., water table depth, herb, and shrub cover) and landscape scale factors (e.g., edge density and human disturbance). The higher abundance of long-distance migrants and insectivores at inside sites suggests PAs are providing critical additional support to key guilds that are in steep decline.